Retrospective analysis of 30 cases of pilonidal sinus by various techniques of conservative and surgical management and review of literature - Karandikar, Sangram; Naik, Narendra G. (International Surgery Journal, 2016)
Background:The pilonidal sinus disease may present as chronic cutaneous infection, pilonidal abscess, pilonidal sinus or recurrent pilonidal sinuses. There are several conservative non-surgical and surgical methods of treatment of pilonidal sinus. The wound healing of pilonidal sinus depends upon multiple factors such as the stage at which patient presented to the surgeon, co-existing medical conditions, method of medical/surgical treatment chosen and the expertise of the surgeon. Here we are presenting the retrospective analysis of 30 cases of pilonidal disease, in view of different modalities of treatment, challenges faced, post-operative results and hospital stay. Methods: Over a period of 7 years, 30 patients suffering from various stages of pilonidal sinus disease were treated by conservative and surgical methods. The choice of treatment modality offered to each patient was individualized based on the stage and severity at the time of presentation. The patients were followed up to assess recurrence for 1 year after complete healing of the pilonidal sinus. Results:All patients with pilonidal sinus/ ulcer < 5 mm showed complete healing without recurrence with conservative line of management. There was recurrence of sinus in 80 % patients treated with only Incision and Drainage for pilonidal sinus abscess. The patients with large sinus (> 5 mm ulcer or skin involvement), were treated by excision with healing by secondary intension. This group of patients was associated with recurrence in 80% cases. The remaining patients with large pilonidal sinus disease were treated by the newer technique of semi-closed method with drain. In this group, only 20% patients developed recurrent sinus. All patients with recurrences healed after either conservative method or surgical method involving local skin flap. Conclusions:The conservative method of treatment is suitable for early and superficial pilonidal sinuses. For chronic and extensive pilonidal sinus disease, surgical treatment with the newer technique of semi-closed method with drain was found to reduce the rate of recurrence. The cases with superficial recurrent pilonidal sinuses may heal with conservative approach and extensive recurrent lesions require reconstruction with local skin flap. The results of the newer technique of semi-closed method with drain were found to be comparable with that of surgery by excision with primary closer. These results may be further evaluated at high volume centre for practical statistical significance regarding choice of treatment.